2005
DOI: 10.1261/rna.7220505
|View full text |Cite
|
Sign up to set email alerts
|

Structural RNA has lower folding energy than random RNA of the same dinucleotide frequency

Abstract: We present results of computer experiments that indicate that several RNAs for which the native state (minimum free energy secondary structure) is functionally important (type III hammerhead ribozymes, signal recognition particle RNAs, U2 small nucleolar spliceosomal RNAs, certain riboswitches, etc.) all have lower folding energy than random RNAs of the same length and dinucleotide frequency. Additionally, we find that whole mRNA as well as 5-UTR, 3-UTR, and cds regions of mRNA have folding energies comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
202
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(213 citation statements)
references
References 37 publications
10
202
0
1
Order By: Relevance
“…Although distinct ordered structures may exist, the overall degree of secondary structure as measured by the lowest free energy of possible folds of noncoding regions of mRNA was not seen to be different from random sequence or from coding sequence (Workman and Krogh 1999;Rivas and Eddy 2000;Clote et al 2005). …”
Section: Single Sequence Structure Prediction Thermodynamicsmentioning
confidence: 94%
“…Although distinct ordered structures may exist, the overall degree of secondary structure as measured by the lowest free energy of possible folds of noncoding regions of mRNA was not seen to be different from random sequence or from coding sequence (Workman and Krogh 1999;Rivas and Eddy 2000;Clote et al 2005). …”
Section: Single Sequence Structure Prediction Thermodynamicsmentioning
confidence: 94%
“…RNAZ [148], a development of RNAalifoldz [147], is a Support Vector Machine classifier that uses two scores to classify multiple alignments as ncRNA or not: z-scores 23 of the individual sequences from the input alignment and a structure conservation index (SCI). The last is given by E A /E, where E A is the alignment thermodynamic score given by the RNAalifold and E is the average free energy of the individual sequences (given by the RNAfold).…”
Section: Comparative Methodsmentioning
confidence: 99%
“…Since the program outputs the free-energy of the alignment, this can be used to calculate the alignment's 22 We can say that "other" means "I have no idea". 23 The z-score computation needs the average and standard deviation of the scores of negative sequences. Often, these measures are calculated using shufflings of the input sequence.…”
Section: Comparative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNAs that are under long-time selection for secondary structure can be expected to have sequences that are more resilient against mutations (Wagner and Stadler, 1999;Nimwegen et al, 1999), which in turn correlates with increased thermodynamic stability of the fold. Indeed, it has been observed that functional RNAs are more stable than the structures formed by randomized sequences (Bonnet et al, 2004;Washietl and Hofacker, 2004;Clote et al, 2005). The program RNAz (Washietl et al, 2005a) combines both approaches.…”
Section: Introductionmentioning
confidence: 99%